Keberhasilan Semu Deradikalisasi di Indonesia - Febriane, Sarie; M, Mariamah (Global: Jurnal Politik Internasional, 2013)
This paper researches the claim made by the Indonesian government regarding the deradicalization program that it ran to deradicalize militants. The Indonesian government claimed that the deradicalization program had been very successful and effective in countering religious extremism. This paper will examine the effects of the de-radicalisation program and will argue that the program has not been as effective as has been claimed. This paper highlights researches which indicate that the program doesn't have a clear structure and the facts that it has been used by terrorist suspects to leave prison through using rewards received after joining the program and rather than being 'de-radicalised' have returned to their terrorist networks and involvement in serious terrorist activities and planning. Whilst the effectiveness of deradicalization program had been claimed by the Indonesian government, this paper argues that the current weak structure of the Indonesian prison system has contributed to the ineffectiveness of the disengagement and deradicalization process. This paper also looks at how the deradicalization program had been used primarily as the purpose of data gathering. Finally this paper will end by proposing recommendation for improving and strengthening the prison system in Indonesia to strengthen disengagement process.